Efficacy of toripalimab in combination with anlotinib in recurrent undifferentiated pleomorphic sarcoma of the sinonasal region: a case report with biomarker analysis - Wu, Fang; Feng, Junqiao; Wang, Hong; Wang, Shan; Cui, Xiaoguang; Liu, Ying; Yan, Linli; Ye, Kaihong; Thorne, Rick F.; Zhang, Xu Dong; La, Ting (Frontiers in Immunology, 2025)
BackgroundSoft tissue sarcoma (STS) typically originates in the muscles and is associated with a poor prognosis. Undifferentiated pleomorphic sarcoma (UPS) is the most commonly diagnosed subtype of STS; however, UPS occurring in the sinonasal region is exceedingly rare and lacks effective treatment options.ObjectiveThis case report presents a patient with sinonasal UPS who experienced disease progression after surgery and chemotherapy but showed a positive response to combination therapy with toripalimab and anlotinib. Additionally, it explores the underlying biomarkers associated with this case.CaseA 63-year-old woman with no significant past medical history was diagnosed with sinonasal UPS. The lesions recurred despite seven extensive surgical resections, and standard chemotherapy failed to control the disease, leading to progressive disease (PD).ResultsThe patient was treated with a combination of toripalimab and anlotinib, resulting in a significant partial response (PR) after just two cycles. Continued PR was observed after an additional six cycles, indicating the potential for a prolonged response with ongoing therapy. Genotyping and immunohistochemistry revealed that the sarcoma cells were rapidly dividing and enriched in vasculature prior to systemic treatment.ConclusionThese findings suggest that the combination of toripalimab and anlotinib may be an effective treatment option for advanced cases of UPS in the sinonasal region.